Investigation of Nutrition-Exercise Behaviors of Students Studying at the Faculty of Sports Sciences - Arslanboğa, Ramazan; Turhan, Muhammed Özkan (Akan BAYRAKDAR, 2025)
[Abstract Not Available]
Keywords: Spor ve Beslenme; Egzersiz ve Spor Bilimleri (Diğer)